On the two-loop divergences of the 2-point hypermultiplet supergraphs for 6D, N=(1,1) SYM theory; Physics Letters B; Vol. 778 - Bukhbinder G. L. Georgy Lvovich; Ivanov E. A. Evgenyi; Merzlikin B. S. Boris Sergeevich; Stepanjyants K. V. Konstantin Viktorovich (2018, 2018)
Title screen